Stretch after the match, not before - Knudson, D. (coachesinfo.com)
One of the most pervasive myths in sports is the belief that stretching before activity improves performance and reduces the risk of injury. Over a decade of biomechanical research on the acute and long-term responses of muscle to stretching has begun to show that this traditional teaching is wrong. Stretching is most effective for increasing range of motion when conducted during the cool-down phase of a workout. This column will summarize the best warm-up and cool-down protocols for tennis play, and briefly review why the performance benefits of stretching are a myth.